Population-based assessment of visual acuity outcomes following cataract surgery in Australia: the National Eye Health Survey. Issue 10 (4th January 2018) - Keel, Stuart; Xie, Jing; Foreman, Joshua; Taylor, Hugh R; Dirani, Mohamed
Abstract : Aim: To assess the visual outcomes of cataract surgery among a national sample of non-Indigenous and Indigenous Australians. Methods: This was a population-based study of 3098 non-Indigenous Australians (50–98 years) and 1738 Indigenous Australians (40–92 years), stratified by remoteness. A poor postoperative outcome in an eye that had undergone cataract surgery was defined as presenting distance visual acuity (PVA) <6/12–6/60, and a very poor outcome was defined as PVA <6/60. Effective cataract surgery coverage (eCSC; operated cataract and a good outcome (PVA ≥6/12) as a proportion of operable plus operated cataract) was calculated. Results: The sampling weight adjusted cataract surgery prevalence was 19.8% (95% CI 17.9 to 22.0) in non-Indigenous Australians and 8.2% (95% CI 6.0 to 9.6) in Indigenous Australians. Among the non-Indigenous population, poor and very poor PVA outcomes were present in 18.1% and 1.9% of eyes, respectively. For Indigenous Australians, these values were 27.8% and 6.3%, respectively. The main causes of poor vision were refractive error (non-Indigenous=41.8%; Indigenous=41.9%) and coincident disease (non-Indigenous=43.3%; Indigenous=40.3%). The eCSC rates in the non-Indigenous and Indigenous populations were 88.5% (95% CI 85.2 to 91.2) and 51.6% (95% CI 42.4 to 60.7), respectively. Conclusion: Approximately half of eyes with a poor visual outcome postcataract surgery could be readily avoided through the appropriate refractive correction. The finding of a lower eCSC rate among Indigenous Australians suggests that improvements in access and quality of cataract services may be warranted in order to reduce cataract-related vision loss in the Indigenous population.